Identification of molecular markers for developing breeding strategies in rose - Cinu Sebastian (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2007)
Rose, one of the most important flowering ornamentals is a favourite for landscaping and an important commercial cut flower. Breeders are always looking for new and novel varieties to meet the ever increasing demand of consumers. However, many years are required to develop a new variety through conventional methods.